2007
DOI: 10.1080/13504850500438736
|View full text |Cite
|
Sign up to set email alerts
|

Decentralization as a determinant of health care expenditure: empirical analysis for OECD countries

Abstract: Territorial decentralization involves the transfer of responsibilities from a central government to lower levels of government. A common trend in different developed countries has been to decentralize some health functions (managerial and/or financial) to local governments. The set-up of the health care system and its degree of decentralization are here utilized in a panel data analysis as a determinant of health care expenditure in a sample of 20 Organization for Economic Co-operation and Development (OECD) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 4 publications
(5 reference statements)
0
28
1
3
Order By: Relevance
“…For example, in studies for European countries, OECD countries and US states, respectively, Christiansen et al . (), Mosca () and Wang () call the attention to the importance of the number of physicians, hospital beds, diagnostic and treatment technologies, and the centralization/decentralization of health care system.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For example, in studies for European countries, OECD countries and US states, respectively, Christiansen et al . (), Mosca () and Wang () call the attention to the importance of the number of physicians, hospital beds, diagnostic and treatment technologies, and the centralization/decentralization of health care system.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Besides income, population structure and medical/technological progress, other factors are considered in the literature to explain health care expenditure: percentage of urban population (Leu, 1986;Gerdtham et al, 1992;Wang, 2009;Hosoya, 2014), female labor force participation (Gerdtham et al, 1992;Christiansen et al, 2006;Hosoya, 2014), health care systems characteristics (Gerdtham et al, 1992;Hitiris and Posnett, 1992;Barros, 1998;Christiansen et al, 2006;Mosca, 2007;Wang, 2009;Baltagi and Moscone, 2010;Hosoya, 2014) and health care supply (Gerdtham et al, 1992;Christiansen et al, 2006;Mosca, 2007;Wang, 2009;Magazzino and Mele, 2012;Hosoya, 2014).…”
Section: Notesmentioning
confidence: 99%
“…While income elasticities above one were usually found in older bivariate cross-sectional or time-series studies, in more recent panel analysis considering non-stationarity and cointegration, and controlling for non-income determinants, the results are more divergent. Most of them have found income elasticities equal or below one, suggesting that healthcare is not a luxury good Dreger and Reimers, 2005;Wang, 2011;Hartwig, 2008;Lago-Peñas et al, 2013;Baltagi and Moscone, 2010;Sen, 2005;Mosca, 2007;Chakroun, 2010a;Hartwig and Sturm, 2014;Hosoya, 2014;Blazquez-Fernandez et al, 2014;Tian et al, 2018;Barros, 1998;Herwartz and Theilen, 2003), but some authors conclude the opposite (Roberts, 1999;Mehrara M, 2010;Yu et al, 2015;.…”
Section: Income Ageing and Healthmentioning
confidence: 99%
“…These variables were found to be relevant by several authors Dreger and Reimers, 2005;Chakroun, 2010b;Lago-Peñas et al, 2013;Mosca, 2007;Hartwig and Sturm, 2014;Yu et al, 2015;, but many other studies have concluded for the irrelevance of the demographic factor Roberts, 1999;Baltagi and Moscone, 2010;Sen, 2005;Hosoya, 2014;Blazquez-Fernandez et al, 2014;Barros, 1998;Herwartz and Theilen, 2003). The inclusion of health-related variables is less common in OECD studies, and very few found these indicators to be significant (Dreger and Reimers, 2005;Tian et al, 2018).…”
Section: Income Ageing and Healthmentioning
confidence: 99%
“…The governments exhibit different levels and types of decentralization-politically, administratively, and fiscally (Mosca 2007;Stegarescu 2004). The governments exhibit different levels and types of decentralization-politically, administratively, and fiscally (Mosca 2007;Stegarescu 2004).…”
Section: Observations and Propositions About Good Governmentmentioning
confidence: 99%